2014
DOI: 10.1007/s11207-014-0585-8
|View full text |Cite
|
Sign up to set email alerts
|

Bridging EUV and White-Light Observations to Inspect the Initiation Phase of a “Two-Stage” Solar Eruptive Event

Abstract: The initiation phase of CMEs is a very important aspect of solar physics, as these phenomena ultimately drive space weather in the heliosphere. This phase is known to occur between the photosphere and low corona, where many models introduce an instability and/or magnetic reconnection that triggers a CME, often with associated flaring activity. To this end, it is important to obtain a variety of observations of the low corona in order to build as clear a picture as possible of the dynamics that occur therein. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 62 publications
2
31
0
1
Order By: Relevance
“…In a recent work, there was a similar "two-stage" eruption scenario that was reported by Byrne et al (2014) for the eruptive event on 2011 March 8. The source region of the erupting flux rope in this event was exactly at the western limb for AIA observations.…”
Section: Summary and Discussionsupporting
confidence: 60%
“…In a recent work, there was a similar "two-stage" eruption scenario that was reported by Byrne et al (2014) for the eruptive event on 2011 March 8. The source region of the erupting flux rope in this event was exactly at the western limb for AIA observations.…”
Section: Summary and Discussionsupporting
confidence: 60%
“…A filament after the first jump decelerates and stops at a greater height as in failed eruptions, but after a rather short period of time it starts to rise again and develops into the successful eruption with a CME formation. Byrne et al (2014) observed on 2011 March 8 at the solar limb the erupting loop system that stayed in a matastable intermediate position for an hour and then proceeded and formed the core of a CME. Gosain et al (2016) analyzed observations of the eruption of a long quiescent filament on 2011 October 22 observed from three viewpoints by space observatories.…”
Section: Introductionmentioning
confidence: 99%
“…The green and yellow dotted lines are the same as those described for figure 1. based on their location with respect to the POS, as it is the case for white-light coronagraph images. Therefore, any coronal feature, such as the erupting loop system studied in Byrne et al (2014), which lies away from the POS will appear as different morphological structures in EUV and white-light observations. Coronal cavities are extended tunnel like structures which are mostly associated with the polar crown filaments (Gibson 2015).…”
Section: Observations Of the Coronal Cavity During Quiescent Phasementioning
confidence: 99%
“…Mierla et al 2013a) and the evolution of a large-scale coronal pseudostreamer in association with cavity system (Guennou et al 2016). SWAP observations also have been used in conjunction with the ground-based Mauna Loa Solar Observatory (MLSO) Mark-IV K-coronameter (Mk4: Elmore et al 2003) to study the initiation phase of a two stage eruptive event (Byrne et al 2014).…”
Section: Introductionmentioning
confidence: 99%